A Tailored DNA Nanoplatform for Synergistic RNAi‐/Chemotherapy of Multidrug‐Resistant Tumors. (23rd October 2018) - Liu, Jianbing; Song, Linlin; Liu, Shaoli; Zhao, Shuai; Jiang, Qiao; Ding, Baoquan
Abstract: Multidrug resistance (MDR) is a major obstacle in the clinical treatment of cancer. Herein, a facile strategy is reported to construct a versatile DNA nanostructure as a co‐delivery vector of RNA interference (RNAi) and chemodrugs to combat multidrug‐resistant tumor (MCF‐7R) in vitro and in vivo. In the tailored nanocarrier, two linear small hairpin RNA (shRNA) transcription templates targeting MDR‐associated genes (gene of P‐glycoprotein, a typical drug efflux pump; and gene of survivin, a representative anti‐apoptotic protein) are precisely organized in the chemodrug (doxorubicin, DOX) pre‐loaded DNA origami. With the incorporation of active targeting and controlled‐release elements, these multifunctional DNA nanocarriers can successfully enter the target MCF‐7R cells and synergistically inhibit tumor growth without apparent systemic toxicity. This tailored DNA nanoplatform, which combines RNAi therapy and chemotherapy, provides a new strategy for the treatment of multidrug‐resistant tumors.